Perancangan Dan Pembuatan Starting Motor DC Shunt 4 Step Menggunakan Variasi Tahanan Berbasis Mikrokontroller ATMega8535 - Sultoni Amni; Noveri Lisbetty Marpaung; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The need for knowledge will never become the student, students, and the society.Along with diminishing labor electrical engineering lab work equipment in universities and riau diciptakanlah the new lab work to create a starting motor direct current detention before using in order to support the process of learning and to provide knowledge to stick together.The test is done to three blocks chain, namely, the relay prisoners startingand current starting.Starting on tampa load the prisoners semangkin small will produce a current of starting a large while the one-time prisoners generator inversely against the current starting at 10 percentage of the average data error 3,863 % and percentages 96,1936 %.Keywords: Starting Motor DC Shunt, Mikrokontroller ATMega8535.